Making cassava safer for consumers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
After rice and maize, cassava is the third most important crop in the tropics. It is a staple for 500 million people in rural Africa, Asia and South America, but can be extremely toxic. In the last 10 years in Zaire and Mozambique alone, 10,()(10...